2019
DOI: 10.1177/1071100719891157
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Patient Reported Outcomes (PRO) Study Assessing Outcomes of Surgically Managed Ankle Fractures

Abstract: Background: Ankle fractures are a common cause of morbidity that have increased in incidence over the past decade. The purpose of this study was to compare the outcomes and prognosis of various fracture subtypes by using 2 validated patient-reported outcome measures: the Patient-Reported Outcome Measurement Information System (PROMIS) Physical Function (PF) and Pain Interference (PI) Computer Adaptive Tests (CATs). Methods: Twelve-month postoperative PF and PI CATs were collected for 126 ankle fracture patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Gilley et al also found a nonnormal distribution of postoperative PROMIS Physical Function scores across fracture subtypes, with worse PROMIS Physical Function scores in patients with bimalleolar and trimalleolar involvement, when compared to isolated medial, lateral, and posterior malleolar fractures. 11 Our results support that trimalleolar fractures are associated with worse patient-reported outcomes as measured by PROMIS. However, it is important to consider that our sample size of 19 patients in the bimalleolar ankle fracture group is small compared to our larger sample size of trimalleolar fractures, which may decrease the strength of this finding.…”
Section: Discussionsupporting
confidence: 79%
“…Gilley et al also found a nonnormal distribution of postoperative PROMIS Physical Function scores across fracture subtypes, with worse PROMIS Physical Function scores in patients with bimalleolar and trimalleolar involvement, when compared to isolated medial, lateral, and posterior malleolar fractures. 11 Our results support that trimalleolar fractures are associated with worse patient-reported outcomes as measured by PROMIS. However, it is important to consider that our sample size of 19 patients in the bimalleolar ankle fracture group is small compared to our larger sample size of trimalleolar fractures, which may decrease the strength of this finding.…”
Section: Discussionsupporting
confidence: 79%
“…However, we believe that the general recovery pattern is likely similar, which is supported in the literature as well. 9 Further, all ankle fractures in our study were operatively managed. Additionally, previous studies have also evaluated clinical outcomes across multiple different ankle fracture types as a single patient sample.…”
Section: Discussionmentioning
confidence: 90%
“…Dean et al 19 reported a mean PROMIS PF T score of 51.9 and PI T score of 47.8 in 142 patients with ankle fracture at a mean of 6 years of follow-up. Gilley et al 20 reported a mean PF T score of 48 in 44 patients with trimalleolar ankle fracture. The mean PF T score of 46 and PI T score of 51 in this study is reasonable given previous reported results in patients with ankle fractures.…”
Section: Discussionmentioning
confidence: 99%